Relative Humidity Sensor Based on Microfiber Loop Resonator. (3rd September 2013) - Zheng, Yangzi; Dong, Xinyong; Zhao, Chunliu; Li, Yi; Shao, Liyang; Jin, Shangzhong
Abstract : A novel relative humidity (RH) sensor based on a microfiber loop resonator (MLR) is proposed and experimentally demonstrated. As refractive index of the microfiber in the MLR is modified by environmental humidity, resonant wavelength of the MLR changes with RH level. By detecting this wavelength shift, RH measurement is realized with a linear response sensitivity of 1.8 pm/% RH. The obvious advantage of this technique over others is that no coating of humidity-sensitive material is required.